Development of TOEFL Apps (El-Lab) during Pandemic Era in the Language Laboratory of Ma'arif Islamic Institute (IAIM) NU Metro -Lampung - Hidayatullah, Rizky; Choirudin, Choirudin; Ari Saputra, Andika; Risky Amalia, Dian; Rahman, Faisal (FOSTER: Journal of English Language Teaching, 2021)
The aims of the research develop TOEFL apps to change the offline to the online system because pandemic era, the online system is not only in TOEFL Test but also in the service of language laboratory of IAIMNU Metro that changes from offline system to online system. Changing the offline system to an online system is certainly not an easy thing for language laboratory officers, because from the registration system to the test system must be held in the online form. the use of technological advances needs to be carried out by language laboratory officers from registration, participant data collection, tutorial scheduling, tutorial systems and TOEFL test. In this study, the authors consider the affective domain phenomenon in language learning. The author uses a qualitative approach to investigate and analyze the results of student interviews which are the influence of two languages on student performance at the Islamic Institute of Islamic Studies Ma'arif NU Metro. In qualitative research, discussion about participation and research location. The research methodology used by the researcher is descriptive qualitative research because this research requires the development of English material. the development model can be developed on three models: procedural, conceptual, and theoretical. The result of this research is the convenience for test participants and also the TOEFL tutorial at IAIMNU Metro, marked with students can feel fast and also the design of the apps is quite easy to understand.